TORGA, Miguel. Los primeros poemas del Diário. Odas. Traducción de Amador Palacios. Mérida: Editora Regional de Extremadura, 2018, 188 p. - Dasilva, Xosé Manuel (2020)
TORGA, Miguel. Los primeros poemas del Diário. Odas. Traducción de Amador Palacios. Mérida: Editora Regional de Extremadura, 2018, 188 p.